Alterations of white matter tracts following neurotoxic hippocampal lesions in macaque monkeys: A diffusion tensor imaging study - Shamy, J.L.; Carpenter, D.M.; Fong, S.G.; Murray, E.A.; Tang, C.Y.; Hof, P.R.; Rapp, P.R. (Hippocampus, 2010)
Diffusion tensor imaging (DTI) is a valuable tool for assessing presumptive white matter alterations in human disease and animal models. The current study used DTI to examine the effects of selective neurotoxic lesions of the hippocampus on major white matter tracts and anatomically related brain regions in macaque monkeys. Two years postlesion, structural MRI, and DTI sequences were acquired for each subject. Volumetric assessment revealed a substantial reduction in the size of the hippocampus in experimental subjects, averaging 72% relative to controls, without apparent damage to adjacent regions. DTI images were processed to yield measures of fractional anisotropy (FA), apparent diffusion coefficient (ADC), parallel diffusivity (lADC), and perpendicular diffusivity (tADC), as well as directional color maps. To evaluate potential changes in major projection systems, a region of interest (ROI) analysis was conducted including the corpus callosum, fornix, temporal stem, cingulum bundle, ventromedial prefrontal white matter, and optic radiations. Lesion‐related abnormalities in the integrity of the fiber tracts examined were limited to known hippocampal circuitry, including the fornix and ventromedial prefrontal white matter. These findings are consistent with the notion that hippocampal damage results in altered interactions with multiple memory‐related brain regions, including portions of the prefrontal cortex. © 2010 Wiley‐Liss, Inc.